THE EFFECT OF THE ACCESSIBILITY TO MENSTRUAL PRODUCTS YOUNG GIRLS' HEALTH AND EDUCATION IN NIGERIA - Doris Lami Madugu; Rosemary Onchi Daniel (International Studies Journal)
This study explores the profound impact of accessibility to menstrual products on the health and education of young girls. The problem is framed around the significant barriers young girls face in accessing safe, affordable, and effective menstrual products, leading to severe health implications and educational setbacks. Using a theoretical framework that integrates gender inequality and social determinants of health, this research investigates the physical, psychological, and social dimensions of menstrual health. Employing quantitative and qualitative methods of data collection, the study utilized 363 questionnaires and 10 in-depth interview which ensured the study gathered rich and robust data from young girls and women, capturing their personal experiences and struggles with menstrual hygiene management. The findings reveal that inadequate access to menstrual products often results in reproductive tract infections and other health complications due to poor hygiene practices. Educationally, many girls miss school during their periods, leading to lower academic performance and widening gender disparities. The pervasive stigma and social taboos surrounding menstruation further exacerbate psychological distress and social exclusion. Based on these findings, the study recommends comprehensive policy interventions to ensure the availability of menstrual products, community engagement to break down stigmas, and education programs to promote menstrual health awareness. This research highlights the critical importance of accessible menstrual products in enhancing the overall well-being of young girls, advocating for sustained efforts to eliminate barriers and promote gender equality, thereby enabling young girls to lead healthier, more empowered lives.